Socioeconomic Burden of Pulmonary Embolism in Europe: Shifting Priorities and Challenges for Novel Reperfusion Strategies - Mohr, Katharina; Barco, Stefano; Neusius, Thomas; Konstantinides, Stavros (Thrombosis and Haemostasis, 2025)
In-hospital case fatality related to acute pulmonary embolism (PE) has been falling since the beginning of this century. However, annual incidence rates continue to climb, and an increasing number of PE survivors need long-term follow-up, chronic anticoagulation treatment, and readmission(s) to the hospital. In European countries, median reimbursed hospital costs for acute PE are still moderate compared with the United States but can increase several-fold in patients with comorbidities and those necessitating potentially life-saving reperfusion treatment. The use of catheter-directed treatment (CDT) has constantly increased in the United States since the past decade, and it has now entered a rapid growth phase in Europe as well, estimated to reach an annual penetration rate of up to 31% among patients with intermediate–high- or high-risk PE by 2030. Ongoing randomised controlled trials are currently investigating the clinical efficacy and safety of these devices. In addition, they will deliver data permitting calculation of their cost-effectiveness in different health care reimbursement systems, by revealing the extent to which they can reduce complications and consequently the need for intensive care and the overall length of hospital stay. After discharge, key cost drivers are related to chronic cardiopulmonary diseases (other than PE itself) leading to frequent readmissions, persistent symptoms, and functional limitations which result in poor quality of life, productivity loss, and substantial indirect costs. Implementation of structured outpatient programmes with a holistic approach to post-PE care, targeting overall cardiovascular health and the patient's well-being, bears the potential to cost-effectively reduce the overall socioeconomic burden of PE.
Keywords: pulmonary embolism; burden of disease; catheter-directed treatment; cost effectiveness